Program book of the 2nd International Materials, Industrial & Manufacturing Engineering Conference (MIMEC 2015) - Denni Kurniawan; Fethma M.Nor
This international conference is intended to be a platform for information dissemination, gathering and networking for academia, researchers and engineers or professional within the area of materials of engineering, industrial engineering and manufacturing engineering, as well as those working /researching/ studying in the related fields